Low-temperature joining of silicon carbide via Al-air in situ reaction. Issue 18 (15th December 2019) - Xue, Jia-Xiang; Shu, Rui; Liao, Ye-Hong; Zhai, Jian-Han; Ma, Hai-Bin; Liu, Tong; Ren, Qi-Sen; Guo, Wei-Ming; Sun, Shi-Kuan; Lin, Hua-Tay
Abstract: In order to achieve pressureless joining of SiC materials at low temperature, an innovative method involving brazing-bonding and in situ oxidation was developed in this work. In contrast to traditional Al brazing bonding or Al2 O3 liquid-phase joining, aluminum-air (Al-air) joining served the dual purpose of joining with metallic Al and subsequently converting to Al2 O3 at a low processing temperature of 1000 °C. Complete conversion of Al to Al2 O3 was evidenced after heat-treating at 1000 °C for 10 h, with a relatively high shear strength of 128.3 MPa. The work here demonstrated the process of Al-air joining was facile and potential for the low-temperature joining of SiC materials, negating the need for external pressure.